A Suspended Stripline Frequency Tripler Using a Left-Handed Nonlinear Transmission Line. (22nd February 2015) - Kim, In Bok; Kim, Hongjoon; Choi, Hyun Chul; Kim, Kang Wook
Abstract : A suspended stripline frequency tripler using a left-handed nonlinear transmission line (LH NLTL) is presented. The proposed tripler using the LH NLTL is composed of a series of varactor diodes, shunt inductances, and a high-pass filter implemented with suspended stripline (SSL). An ultrawideband microstrip-to-suspended stripline transition is also utilized. The fabricated LH NLTL provides the minimum insertion loss of 1.7 dB and the maximum insertion loss of 4.7 dB for a wide frequency band from 2.6 to 18 GHz. As a tripler, the measured minimum third harmonic conversion loss is 15.3 dB at an input frequency of 2.4 GHz and typically 17 dB from 2 to 3.1 GHz.